2014
DOI: 10.1136/annrheumdis-2013-205139
|View full text |Cite
|
Sign up to set email alerts
|

Treat-to-target in systemic lupus erythematosus: recommendations from an international task force

Abstract: The principle of treating-to-target has been successfully applied to many diseases outside rheumatology and more recently to rheumatoid arthritis. Identifying appropriate therapeutic targets and pursuing these systematically has led to improved care for patients with these diseases and useful guidance for healthcare providers and administrators. Thus, an initiative to evaluate possible therapeutic targets and develop treat-to-target guidance was believed to be highly appropriate in the management of systemic l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
432
0
55

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 610 publications
(519 citation statements)
references
References 112 publications
10
432
0
55
Order By: Relevance
“…Further studies have shown that patients with a prolonged SACQ disease accumulate less damage, supporting the idea of managing them with close monitoring without therapy during this period (15,16).…”
Section: Discussionmentioning
confidence: 88%
“…Further studies have shown that patients with a prolonged SACQ disease accumulate less damage, supporting the idea of managing them with close monitoring without therapy during this period (15,16).…”
Section: Discussionmentioning
confidence: 88%
“…Long-term monitoring was recommended (10,14), with 3-6 month assessment for mild disease and increased frequency for patients with severe active disease and in pregnancy (10). Patients with nonactive SLE and no damage or comorbidity could be assessed every 6 to12 months with additional evaluation prior to pregnancy, surgery, transplantation, use of estrogen-containing medication, or occurrence of a new neurologic or vascular event (11).…”
Section: Resultsmentioning
confidence: 99%
“…Six guidelines provided recommendations on monitoring disease activity, disease damage, and quality of life (10)(11)(12)(13)(14)(15).…”
Section: Resultsmentioning
confidence: 99%
“…Since damage predicts subsequent death, prevention of damage accrual should be a major therapeutic goal in SLE. SELENA SLEDAI Disease Assessment Scale and SLICC/ACR Damage Index are recommended for assessment of SLE activity and damage [8]. …”
Section: Introductionmentioning
confidence: 99%